Spontaneous renal subcapsular fluid accumulation with hemorrhage due to ureteral stone: a case report and literature review - Hu, Yudong; Wang, Xiaofeng; Chen, Yujie; Li, Jun; Zhu, Faming; Yuan, Ye; Ye, Jin; Yang, Fan; Zhong, Yong (Frontiers in Surgery, 2025)
BackgroundSubcapsular or perirenal hemorrhage is a serious complication commonly associated with exogenous trauma and medical interventions. However, spontaneous subcapsular or perirenal hemorrhage can occur in the absence of known trauma, presenting as a rare but potentially life-threatening urological condition.Case presentationThis case report describes a 59-year-old female patient who presented with left flank pain as the main symptom, with no history of trauma. An enhanced abdominal computerized tomography (CT) scan revealed a left upper ureteral stone, severe left hydronephrosis, and left renal subcapsular fluid accumulation with hemorrhage. Following 2 weeks of conservative treatment, the patient underwent double-J ureteral stent insertion after stabilization of the left renal subcapsular hemorrhage. The stent was regularly replaced, and follow-up CT scans were conducted. After the resolution of left renal pelvic effusion and absorption of the left renal subcapsular fluid with hemorrhage, the patient underwent retrograde intrarenal surgery (RIRS), leading to successful treatment.ConclusionsIn cases of spontaneous renal subcapsular fluid accumulation with hemorrhage due to ureteral stone, conservative treatment through ureteral stent placement for renal preservation is worthwhile. Then, management of ureteral stone by second-stage RIRS after absorption of the renal subcapsular hemorrhage is an available option.